1976
DOI: 10.1139/b76-269
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the modifying effect of kinetin on in vitro tuberization of induced and non-induced tissues of Solatium tuberosum

Abstract: ‘Katahdin’ potato plants (Solatium tuberosum L.) were grown under inducing (26 °C day −12 °C night with an 8-h photoperiod) and non-inducing (28 °C day −25 °C night with a 16-h photoperiod) conditions. Apical, medial, and basal nodal stem segments from each plant harvested were surface sterilized and aseptically transferred to culture flasks containing Murashige and Skoog's medium with and without kinetin. After culturing in dark for 4 weeks at 24 °C, percentage tuberization of segments from induced plants was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
2
1

Year Published

1978
1978
1993
1993

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 0 publications
1
14
2
1
Order By: Relevance
“…Results of the present study differed somewhat from others conducted in this laboratory (18 Further evidence that this rise in ZR levels signaled entrance into the state to tuberize comes from an earlier study (12) where we observed that percentage tuberization of nodal stem segments from induced plants was significantly higher than noninduced plants when cultured in vitro. With the addition of kinetin to the medium, however, this relationship was no longer apparent, ie.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…Results of the present study differed somewhat from others conducted in this laboratory (18 Further evidence that this rise in ZR levels signaled entrance into the state to tuberize comes from an earlier study (12) where we observed that percentage tuberization of nodal stem segments from induced plants was significantly higher than noninduced plants when cultured in vitro. With the addition of kinetin to the medium, however, this relationship was no longer apparent, ie.…”
Section: Discussioncontrasting
confidence: 97%
“…Similarly, Palmer and Smith (26) have demonstrated the requirement for cytokinins for in vitro tuberization of excised rhizomes. Results of this laboratory (11,12,18) have supported the theory that the tuberizing factor may be cytokininlike in nature, in that total cytokinin activity was significantly higher in induced than noninduced plants. Two of the four cytokinin compounds separated from potato tissues were significantly higher in induced plants, reaching their highest values in below-ground tissues after 6 'To whom reprint requests should be sent.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…Thus, in vitro derived tubers are valuable for agricultural use because disease free seed plants can be easily transferred, stored and distributed. Culture conditions and techniques for the in vitro propagation of tubers have been studied and improved by numerous researchers3, [5][6][7][8][9][10] Of special note is the liquid shaken culture for rapid propagation of tubers reported by Estrada et al (1986)". Their method is applicable to large scale culture thereby improving the economic advantages12.…”
Section: Introductionmentioning
confidence: 99%
“…Such in vitro propagated tubers are known as microtubers and they have sufficient potential for direct application in field cultivation despite their small size [1][2][3][4] Numerous researchers have been studying the factors affecting in vitro tuberization" [5][6][7][8][9] Labor cost, which is the major obstacle for the industrial production of disease-free plants using in vitro culture techniques, can be reduced by a large scale culture system10). With regard to the rapid propagation of potato microtubers, Estrada et al (1986) first reported a culture method using a liquid shake culture".…”
Section: Introductionmentioning
confidence: 99%